Managers’ Political Beliefs and Gender Inequality among Subordinates: Does His Ideology Matter More Than Hers? - Carnahan, Seth; Greenwood, Brad N. (Administrative Science Quarterly, 2018)
To explore whether managers’ beliefs and attitudes influence gender inequality among their subordinates, we theorize about the relationship between managers’ political ideology, situated on a liberal–conservative continuum, and differences in the hiring, work team selection, and promotion of male versus female subordinates, as well as how a manager’s gender moderates this relationship. We analyze novel microdata from the U.S. legal industry from 2007 to 2012 and find that large law offices whose partners are more liberal hire a larger percentage of female associates, that more-liberal partners are more likely to select female associates to be members of their client teams, and that associates whose supervising partners are more liberal have greater gender parity in promotion rates. Further, we find that the ideology of male partners is significantly more influential than the ideology of female partners in affecting these differences. We find little evidence that sorting on the part of higher-quality female associates drives the results.